Interni: Brandelli di memoria intorno a "La Traviata Norma" - Facchetti, Sergio (Mimesis Journal, 2024)
In this text, Sergio Facchetti argues that the conflicts that led to the dissolution of the COM (Comitati Omosessuali Milanesi) were already present during the production of the theatrical pieceLa Traviata Norma. Remembering the houses interiors of three emblematic figures of the COM (Corrado Levi, Mario Mieli, Francesco Pertegato), the author tries to stress some of the cultural and social differences inside that gay group.